Lead-free piezoelectric ceramic with high mechanical quality factor and high vibration velocity stability and preparation method of lead-free piezoelectric ceramic
By introducing A2+ and B3+ ions into BNT-based ceramics and using two-step prefiring process to construct an oxygen-deficient perovskite structure, the problems of low mechanical quality factor and poor vibration speed stability of BNT-based ceramics are solved, and high mechanical quality is achieved Lead-free piezoelectric ceramic with factor and vibration speed stability, suitable for medium and high power ultrasonic transducers.
Patent Information
- Application Number
- CN202411400985.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The low mechanical quality factor and poor vibration speed stability of BNT-based ceramics lead to serious energy loss and heating problems in high-power piezoelectric devices, which limits its application.
By introducing A2+ and B3+ ions in Bi0.5Na0.5TiO3, pseudoperovskite (Bi0.5-0.5xNa0.5-0.5xAx)(Ti1-xBx)O3-0.5x solid solution ceramics were constructed using a two-step prefiring process. A perovskite structure with oxygen deletion is formed to inhibit domain flip, thereby improving the mechanical quality factor and vibration speed stability.
It significantly improves the mechanical quality factor and vibration speed stability of ceramics. D33 is higher than 120pC/N, Td is higher than 150℃, Qm is higher than 700, and the Qm value is lowered by 5% at high vibration speed, satisfying the medium and high power ultrasonic exchange Application requirements of energy devices.
Smart Images

Figure CN119285350A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of functional ceramic materials, and in particular relates to a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability and a preparation method thereof. Background Art
[0002] Piezoelectric materials can convert electrical energy and mechanical energy and are widely used in electromechanical conversion devices such as sensors, transformers, and transducers. With the improvement of people's environmental protection and health awareness and the requirements of social sustainable development strategies, the production and use of lead-containing materials and related devices are restricted. The research and development of high-performance lead-free piezoelectric ceramics is urgent and of practical significance. 0.5 Na 0.5 TiO3, BNT) is a typical representative of lead-free perovskite materials with excellent electrical properties and strong repeatability. In particular, BNT-based ceramics have a high coercive field (E c ~70kV / cm) and Curie temperature (T m ~300℃), it has unique advantages in the field of high-power ultrasound and has attracted widespread attention.
[0003] High-power piezoelectric devices require piezoelectric materials to have high mechanical quality factor Q m , mechanical quality factor Q m It is the inverse of mechanical loss. The smaller the mechanical loss, the higher Q m The higher the value, the lower the mechanical quality factor of BNT ceramics. m About 300, BNT-based ceramics with rhombohedral-tetragonal quasi-morphous phase boundary components Q m Usually less than 100, such as 0.94BNT-0.06BT and 0.80BNT-0.20BKT systems. m The value causes serious energy loss of BNT-based ceramic materials, aggravates heating, leads to material performance degradation or even failure, and seriously hinders its application in power piezoelectric devices. Therefore, designing methods to improve the mechanical quality factor and high vibration speed stability of BNT-based ceramics has extremely important research value and practical significance. Summary of the invention
[0004] The present invention aims to solve the problems of low mechanical quality factor and poor high vibration speed stability of existing BNT-based ceramics, and to provide a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability and a preparation method thereof.
[0005] A lead-free piezoelectric ceramic with high mechanical quality factor and high vibration speed stability has the general chemical formula (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x, wherein x represents the molar fraction, 0.01≤x≤0.08; the A element is selected from one of Ca, Sr and Ba with divalent ion state, and the B element is selected from one of Co, Sc, Ga, In, Cr, Mn and Fe with trivalent ion state.
[0006] A method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability is completed by the following steps:
[0007] 1. According to Bi 0.5 Na 0.5 TiO3 Proportion Weigh Bi2O3, Na2CO3 and TiO2, mix the weighed Bi2O3, Na2CO3 and TiO2 and place them in a ball mill for ball milling, dry and grind the ball-milled slurry to obtain a mixed powder;
[0008] 2. Place the mixed powder in a corundum crucible and transfer it to a box furnace for pre-sintering to obtain pure perovskite phase Bi 0.5 Na 0.5 Pre-calcined powder of TiO3;
[0009] 3. According to the chemical formula (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Weigh a set amount of pure perovskite phase Bi in a stoichiometric ratio 0.5 Na 0.5 Pre-calcined powder of TiO3, carbonate compound corresponding to element A and oxide corresponding to element B are used as raw materials, wherein x represents molar fraction, 0.01≤x≤0.08; element A is selected from one of Ca, Sr and Ba with divalent ion valence, and element B is selected from one of Co, Sc, Ga, In, Cr, Mn and Fe with trivalent ion valence;
[0010] Fourth, the raw material powder is placed in a mortar and ground thoroughly, and the ground powder is pre-burned twice to obtain (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Powder; the temperature of the second pre-firing is lower than the temperature of the first pre-firing;
[0011] 5. Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5xAdd a binder to the powder, grind it evenly, bake it under a high-temperature searchlight to remove excess moisture, and then sieve it and press it into tablets;
[0012] 6. Place the formed disc in a crucible and use the pure perovskite phase Bi obtained in step 2 0.5 Na 0.5 The pre-burned powder of TiO3 is buried up and down, and sintered after thermal debonding; and then the ceramic sample is obtained after sintering at 920℃~1180℃ for 1~4h;
[0013] 7. The ceramic sample is gold-plated using a small metal sputtering coating machine and polarized using a DC high-voltage power supply. After polarization, a lead-free piezoelectric ceramic with high mechanical quality factor and high vibration speed stability is obtained.
[0014] Beneficial effects of the present invention: The present invention utilizes a two-step pre-sintering process to 0.5 Na 0.5 TiO3 is simultaneously introduced with A 2+ and B 3+ ions, construct pseudoperovskite (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Solid solution ceramics, through valence design, produce oxygen vacancies in the perovskite lattice, forming a distorted perovskite structure, inhibiting domain flipping, thereby improving the mechanical quality factor and high vibration stability of the ceramic. 33 Higher than 120pC / N, T d Above 150℃, Q m Above 700, high vibration speed Q m The value drops by less than 5%, which can meet the application requirements of medium and high power ultrasonic transducers. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 for (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 XRD patterns of ceramics;
[0016] Figure 2 for (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Surface SEM images of ceramics;
[0017] Figure 3for (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Hysteresis loop of ceramics;
[0018] Figure 4 for (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Impedance spectroscopy of ceramics;
[0019] Figure 5 for (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Dielectric temperature spectrum of ceramics; 1 indicates a frequency of 1kHz, 2 indicates a frequency of 10kHz, and 3 indicates a frequency of 100kHz;
[0020] Figure 6 for (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Mechanical quality factor curves of ceramics at different vibration speeds. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any combination of the specific implementation modes.
[0022] Specific implementation method 1: In this implementation method, a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability has the general chemical formula (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x , wherein x represents the molar fraction, 0.01≤x≤0.08; the A element is selected from one of Ca, Sr and Ba with divalent ion state, and the B element is selected from one of Co, Sc, Ga, In, Cr, Mn and Fe with trivalent ion state.
[0023] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the lead-free piezoelectric ceramic with both high mechanical quality factor and high vibration speed stability is a pseudo-perovskite structure with oxygen vacancies. Other aspects are the same as specific embodiment 1.
[0024] Specific implementation method three: In this implementation method, a preparation method of a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability is completed by the following steps:
[0025] 1. According to Bi 0.5 Na 0.5 TiO3 Proportion Weigh Bi2O3, Na2CO3 and TiO2, mix the weighed Bi2O3, Na2CO3 and TiO2 and place them in a ball mill for ball milling, dry and grind the ball-milled slurry to obtain a mixed powder;
[0026] 2. Place the mixed powder in a corundum crucible and transfer it to a box furnace for pre-sintering to obtain pure perovskite phase Bi 0.5 Na 0.5 Pre-calcined powder of TiO3;
[0027] 3. According to the chemical formula (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Weigh a set amount of pure perovskite phase Bi in a stoichiometric ratio 0.5 Na 0.5 Pre-calcined powder of TiO3, carbonate compound corresponding to element A and oxide corresponding to element B are used as raw materials, wherein x represents molar fraction, 0.01≤x≤0.08; element A is selected from one of Ca, Sr and Ba with divalent ion valence, and element B is selected from one of Co, Sc, Ga, In, Cr, Mn and Fe with trivalent ion valence;
[0028] Fourth, the raw material powder is placed in a mortar and ground thoroughly, and the ground powder is pre-burned twice to obtain (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Powder; the temperature of the second pre-firing is lower than the temperature of the first pre-firing;
[0029] 5. Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5xAdd a binder to the powder, grind it evenly, bake it under a high-temperature searchlight to remove excess moisture, and then sieve it and press it into tablets;
[0030] 6. Place the formed disc in a crucible and use the pure perovskite phase Bi obtained in step 2 0.5 Na 0.5 The pre-burned powder of TiO3 is buried up and down, and sintered after thermal debonding; and then the ceramic sample is obtained after sintering at 920℃~1180℃ for 1~4h;
[0031] 7. The ceramic sample is gold-plated using a small metal sputtering coating machine and polarized using a DC high-voltage power supply. After polarization, a lead-free piezoelectric ceramic with high mechanical quality factor and high vibration speed stability is obtained.
[0032] Specific embodiment 4: This embodiment is different from specific embodiment 3 in that: the parameters of the ball milling in step 1 are: the ball-to-material ratio is (1.2-1.5):1, the rotation speed is 180-230 rpm, the ball milling time is 10-20h, and the drying temperature is 80-130°C. Others are the same as specific embodiment 3.
[0033] Specific embodiment 5: This embodiment is different from specific embodiment 3 in that the temperature of the primary pre-firing in step 2 is 750-880° C. and the time is 2-5 hours. The rest is the same as specific embodiment 3.
[0034] Specific embodiment 6: This embodiment is different from specific embodiment 3 in that the temperature of the secondary pre-firing in step 4 is 680-740° C. and the time is 1-3 hours. The rest is the same as specific embodiment 3.
[0035] Specific implementation method 7: This implementation method is different from the specific implementation method 3 in that the adhesive in step 5 is PVA, and the amount of adhesive added is (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x 7% of the mass of the powder; the baking time is 1 to 4 minutes; the mesh number of the sieve is 80 to 120 meshes; the tabletting is performed under a pressure of 4 to 8 MPa to form a round tablet. The rest is the same as the third embodiment.
[0036] Specific embodiment eight: This embodiment differs from specific embodiment three in that: the temperature of the thermal debonding in step six is 550-650°C for 2-4 hours, and the temperature of the sintering is 920-1180°C for 1-4 hours. The rest is the same as specific embodiment three.
[0037] Specific embodiment 9: This embodiment differs from specific embodiment 3 in that: the gold plating time in step 7 is 5 to 15 minutes; the electric field intensity of the polarization treatment is 30 to 70 kV / cm, and the polarization time is 30 to 60 minutes. The rest is the same as specific embodiment 3.
[0038] Specific embodiment 10: This embodiment differs from specific embodiment 3 in that: the lead-free piezoelectric ceramic with high mechanical quality factor and high vibration speed stability described in step 7 has an average grain size of 25 μm, a piezoelectric coefficient higher than 120 pC / N, a thermal transition temperature higher than 150°C, a coercive field of about 40 kV / cm, and a residual polarization strength of about 38 μC / cm 2 , the mechanical quality factor is higher than 700, and the performance degradation rate within the vibration speed of 1m / s is lower than 5%. Other aspects are the same as those of the third embodiment.
[0039] The following examples are used to verify the beneficial effects of the present invention:
[0040] Embodiment 1:
[0041] A method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability is completed by the following steps:
[0042] 1. According to Bi 0.5 Na 0.5 TiO3 Proportion Weigh analytically pure Bi2O3, Na2CO3 and TiO2, mix the weighed Bi2O3, Na2CO3 and TiO2 and place them in a ball mill for ball milling for 15 hours, dry and grind the ball-milled slurry to obtain a mixed powder;
[0043] 2. Place the mixed powder in a corundum crucible and transfer it to a box furnace and calcine at 810°C for 3 hours to obtain pure perovskite phase Bi 0.5 Na 0.5 Pre-calcined powder of TiO3;
[0044] 3. According to the chemical formula (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Weigh a set amount of pure perovskite phase Bi in a stoichiometric ratio 0.5 Na 0.5 Pre-calcined powder of TiO3, BaCO3 and Fe2O3 are used as raw materials;
[0045] Fourth, the raw material powder was placed in a mortar and anhydrous ethanol was added to fully grind, and the evenly ground powder was calcined at 720°C for 1h to obtain (Bi 0.48 Na 0.48Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Powder;
[0046] 5. Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 7wt% PVA was added to the powder, and after being evenly ground, it was baked under a high-temperature searchlight for 2 minutes to remove excess moisture, then sieved through a 100-mesh sieve, and pressed into a 10mm diameter disc at a pressure of 6MPa without holding pressure;
[0047] 6. Place the formed disc in a crucible and use the pure perovskite phase Bi obtained in step 2 0.5 Na 0.5 The pre-sintered powder of TiO3 was buried up and down to reduce the volatilization of elements, and the binder was removed at 600℃ for 2h, and then sintered at 1125℃, kept at this temperature for 1h, with a heating rate of 3℃ / min, and cooled with the furnace to obtain (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Ceramic pieces;
[0048] 7. General (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 The ceramic sheet is plated with gold using a small metal sputtering coating machine and polarized using a DC high voltage power supply. After polarization is completed, (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Piezoelectric ceramics.
[0049] Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 The ceramic pieces were ground into fine powder and their X-ray diffraction spectra were tested at room temperature. Figure 1 As shown, the sample exhibits a pseudoperovskite structure.
[0050] In the pair 0.48 Na 0.48Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 After the surface of the ceramic sample was sputtered with gold electrode, the morphology of the ceramic surface was observed using a scanning electron microscope. Figure 2 The ceramic surface is dense and uniform, with an average grain size of 25 μm, which is higher than the grain size of most BNT-based ceramics reported so far.
[0051] Right(Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 The ferroelectric properties of ceramics were tested. The hysteresis loop was tested at room temperature with an electric field strength of 60 kV / cm and a frequency of 1 Hz. Figure 3 As shown. The ceramic presents a typical hysteresis loop shape, and the coercive electric field E c is 40kV / cm, and the residual polarization intensity P r 38μC / cm 2 .
[0052] The (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 After the ceramic is sputtered with gold electrodes, a DC high voltage power supply is used to polarize the ceramic sheet at 50°C and 50 kV / cm electric field for 10 min. After the polarization is completed, the polarized (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 Piezoelectric ceramics. Using quasi-static d 33 The tester tests its d 33 It is 126pC / N.
[0053] The polarization (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 The dielectric temperature spectrum test is performed on ceramic sheets. The dielectric constant and dielectric loss at different temperatures are measured at different test frequencies. Figure 4 is the dielectric temperature spectrum of the ceramic. First, the ceramic shows frequency dispersion and temperature dispersion in the high temperature region, indicating that the ceramic is a relaxor ferroelectric. Second, the first dielectric anomaly peak of the ceramic is T dThe peak indicates that the thermal transition temperature of the ceramic is 152 °C.
[0054] The polarization (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 The ceramic piece is tested for impedance spectrum, such as Figure 5 The test frequency is 278kHz to 302kHz, the resonant frequency is 283kHz, and the anti-resonant frequency is 297kHz; the phase angle is -87° to 86°, indicating that the polarization is sufficient. The GB mode in the 4294A impedance analyzer is used to test the mechanical quality factor of the sample, Q m It is 716.
[0055] Test (Bi 0.48 Na 0.48 Ba 0.04 )(Ti 0.96 Fe 0.04 ) 0.98 The mechanical quality factor of the ceramic piece at different vibration speeds, such as Figure 6 As shown. The high power piezoelectric characterization system is used to test the Q of the sample at different vibration speeds. m Value, when the vibration speed is low, Q m The value is 722, which is basically consistent with the test result of the impedance analyzer, indicating that the test result is normal; when the vibration speed increases to about 1m / s, Q m The value drops to 690, Q m The value decreased by 4.4%.
Claims
1. A lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability, characterized in that The chemical formula of lead-free piezoelectric ceramics with high mechanical quality factor and high vibration speed stability is (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x , wherein x represents the molar fraction, 0.01≤x≤0.08; the A element is selected from one of Ca, Sr and Ba with divalent ion state, and the B element is selected from one of Co, Sc, Ga, In, Cr, Mn and Fe with trivalent ion state.
2. A lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 1, characterized in that The lead-free piezoelectric ceramic with high mechanical quality factor and high vibration stability is a pseudoperovskite structure with oxygen vacancies.
3. A method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability as claimed in claim 1, characterized in that The preparation method of lead-free piezoelectric ceramics with high mechanical quality factor and high vibration speed stability is completed in the following steps:
1. According to Bi 0.5 Na 0.5 TiO3 Proportion Weigh Bi2O3, Na2CO3 and TiO2, mix the weighed Bi2O3, Na2CO3 and TiO2 and place them in a ball mill for ball milling, dry and grind the ball-milled slurry to obtain a mixed powder; 2. Place the mixed powder in a corundum crucible and transfer it to a box furnace for pre-sintering to obtain pure perovskite phase Bi 0.5 Na 0.5 Pre-calcined powder of TiO3; 3. According to the chemical formula (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Weigh a set amount of pure perovskite phase Bi in a stoichiometric ratio 0.5 Na 0.5 Pre-calcined powder of TiO3, carbonate compound corresponding to element A and oxide corresponding to element B are used as raw materials, wherein x represents molar fraction, 0.01≤x≤0.08; element A is selected from one of Ca, Sr and Ba with divalent ion valence, and element B is selected from one of Co, Sc, Ga, In, Cr, Mn and Fe with trivalent ion valence; Fourth, the raw material powder is placed in a mortar and ground thoroughly, and the ground powder is pre-burned twice to obtain (Bi 0.5- 0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Powder; the temperature of the second pre-firing is lower than the temperature of the first pre-firing; 5. Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x Add a binder to the powder, grind it evenly, bake it under a high-temperature searchlight to remove excess moisture, and then sieve it and press it into tablets; 6. Place the formed disc in a crucible and use the pure perovskite phase Bi obtained in step 2 0.5 Na 0.5 The pre-burned powder of TiO3 is buried up and down, and sintered after thermal debonding; and then the ceramic sample is obtained after sintering at 920℃~1180℃ for 1~4h; 7. The ceramic sample is gold-plated using a small metal sputtering coating machine and polarized using a DC high-voltage power supply. After polarization, a lead-free piezoelectric ceramic with high mechanical quality factor and high vibration speed stability is obtained.
4. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The parameters of the ball milling in step 1 are: the ball-to-material ratio is (1.2-1.5):1, the rotation speed is 180-230 rpm, and the ball milling time is 10-20 h; the drying temperature is 80-130° C.
5. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The temperature of the first pre-calcination in step 2 is 750-880° C. and the time is 2-5 hours.
6. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The temperature of the secondary pre-firing in step 4 is 680-740° C. and the time is 1-3 hours.
7. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The adhesive in step 5 is PVA, and the amount of adhesive added is (Bi 0.5-0.5x Na 0.5-0.5x A x )(Ti 1-x B x ) 3-0.5x 7% of the mass of the powder; the baking time is 1 to 4 minutes; the mesh number of the sieve is 80 to 120 meshes; the tabletting is performed under a pressure of 4 to 8 MPa to form a round tablet.
8. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The temperature of the thermal debonding in step six is 550-650° C., and the time is 2-4 hours; the temperature of the sintering is 920-1180° C., and the time is 1-4 hours.
9. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The gold plating time in step seven is 5 to 15 minutes; the electric field intensity of the polarization treatment is 30 to 70 kV / cm, and the polarization time is 30 to 60 minutes.
10. The method for preparing a lead-free piezoelectric ceramic having both high mechanical quality factor and high vibration speed stability according to claim 3, characterized in that The lead-free piezoelectric ceramic with high mechanical quality factor and high vibration speed stability described in step 7 has an average grain size of 25 μm, a piezoelectric coefficient higher than 120 pC / N, a thermal transition temperature higher than 150°C, a coercive field of about 40 kV / cm, and a residual polarization strength of about 38 μC / cm 2 , the mechanical quality factor is higher than 700, and the performance degradation rate within the vibration speed of 1m / s is less than 5%.
Citation Information
Patent Citations
Ferroelectric material based on metal cation doping and preparation method thereof
CN110372371A
Piezoelectric ceramic and method for manufacturing same, as well as piezoelectric element
CN111662082A
Cited By
Piezoelectric ceramic with high fracture toughness and preparation method and application thereof
CN122878126A